Inguinal Hernia Surgery - Campanelli, Giampiero (Springer Milan : Imprint: Springer, 2017)
This book, which describes in detail the most common procedures employed in inguinal hernia surgery, is exceptional in reflecting fully the most recent advances, as well as the most established techniques, in knowledge and practice. The role of recently developed and emerging technologies, including robotics, minimally invasive surgery, and biological meshes, is clearly explained, highlighting useful tips and tricks. The descriptions of traditional procedures, such as the Lichtenstein repair, are brought fully up to date and take into account the novel perceptions that professionals have of them, for example regarding the important role of nurses. The reader will also find guidance on established and new treatments for specific pain conditions, including postoperative chronic pain, the pubic inguinal pain syndrome, and obscure groin pain in women. The need for such an update on inguinal hernia surgery became clear at the 1st World Conference on Abdominal Wall Hernia Surgery, which highlighted the huge differences in the approaches adopted by scientists around the world and was chaired by the editor of this book. Inguinal Hernia Surgery will be a useful tool for all health care practitioners involved in hernia surgery.
Keywords: Medicine.; Pain medicine.; Abdominal surgery.; Minimally invasive surgery.; elektronické knihy; electronic books